The Principles of Teaching Reading Skill for Educational Section - Moh. Zainol Kamal; Ahmad Effendi (Tafhim Al-'Ilmi, 2021)
Abstract Language is a means of communication. Human beings use a language to communicate with each other in order to express their minds and accomplish their needs. World wide communication, technology, politics, literature, agriculture and science mostly used English as the language. Reading is an important activity in every language. Reading enables people to find out information from a variety of texts, written or printed information from newspapers, magazines, advertisements, brochures and soon. Good English reading comprehension is really needed to be mastered especially by students to face this global era in which the English is the language that is used. Reading comprehension is taught since the first year of junior high school till the university. It indicates that reading comprehension is important.By this skill students can get more information not only from the school, they also can get information from the English magazine, book, journal or everything written in English Keywords:Principles, Teaching Reading